2021
DOI: 10.3390/life11010063
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Wall Reactions to Coronary Stents—Clinical Implications for Stent Failure

Abstract: Coronary stents belong to the most commonly implanted devices worldwide. A number of different types of stent exist, with very different mechanical and biochemical characteristics that influence their interactions with vascular tissues. Inappropriate inflammatory reactions are the major cause of the two major complications that follow implantation of stents in a percentage as high as 5–20%. It is therefore important to understand these reactions and how different they are among different generations of stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 76 publications
0
11
0
1
Order By: Relevance
“…A previous study demonstrated that LSM may cause stent thrombosis. Compared with the control group, the incidence of SM in patients with very advanced thrombosis (77 vs. 12%, respectively; P<0.001) and the area of SM (77 vs. 12%, respectively; P<0.001) were significantly increased ( 68 ). A total of 20 cases of late and very late stent thrombosis were examined through OCT, indicating that 11 cases (55%) had SM, of which 5 cases had LSM caused by abnormal positive remodeling of the vessel wall ( 68 ).…”
Section: Application Of Oct In the Post-stent Implantation Follow-upmentioning
confidence: 84%
See 1 more Smart Citation
“…A previous study demonstrated that LSM may cause stent thrombosis. Compared with the control group, the incidence of SM in patients with very advanced thrombosis (77 vs. 12%, respectively; P<0.001) and the area of SM (77 vs. 12%, respectively; P<0.001) were significantly increased ( 68 ). A total of 20 cases of late and very late stent thrombosis were examined through OCT, indicating that 11 cases (55%) had SM, of which 5 cases had LSM caused by abnormal positive remodeling of the vessel wall ( 68 ).…”
Section: Application Of Oct In the Post-stent Implantation Follow-upmentioning
confidence: 84%
“…Compared with the control group, the incidence of SM in patients with very advanced thrombosis (77 vs. 12%, respectively; P<0.001) and the area of SM (77 vs. 12%, respectively; P<0.001) were significantly increased ( 68 ). A total of 20 cases of late and very late stent thrombosis were examined through OCT, indicating that 11 cases (55%) had SM, of which 5 cases had LSM caused by abnormal positive remodeling of the vessel wall ( 68 ). However, the incidence of LSM is notably higher than the incidence of late stent thrombosis, indicating that, although LSM may not be the sole cause of stent thrombosis, it may be one of the critical factors contributing to the formation of stent thrombosis.…”
Section: Application Of Oct In the Post-stent Implantation Follow-upmentioning
confidence: 84%
“…In this context, thrombin also has potent mitogen effects, and the immunosuppressive effect of the drug eluted might slow tissue repair reaction and fibrin removal. The prolonged activation of the thrombotic cascade concurs with the activation of inflammatory cells (monocytes, T cells, neutrophils), secretion of chemoattractant molecules (MCP-1 or monocyte chemoattractant protein-1, Interleukin (IL)-8) by endothelial and SMCs and the production of growth factors (PDGF, platelet-derived growth factor, bFGF or fibroblast growth factor, TGF or transforming growth factor-beta, IGF, insulin-like growth factor, and VEGF, vascular endothelial growth factor [23]). Platelet-derived extracellular vesicles stimulate SMCs to produce interleukin 6 and express α IIb β 3 and P-selectin, which favor their interaction with monocytes [24].…”
Section: Cells Involved In the Pathophysiology Of In-stent Restenosismentioning
confidence: 94%
“…The pro-thrombotic risk is possible to diminish with the use of corresponding drugs, such as Aspirin + P2Y12 inhibitors. This makes drug-eluting stents a better choice in comparison with bare-metal stents [52].…”
Section: Mtor Modulation In Atherosclerosismentioning
confidence: 99%